Teacher induction policy in global contexts : intentions, implementations, and influences - Wang, Jian, 1960- (Emerald Publishing Limited : Information Age Publishing, Inc., 2024)
"Teacher induction is becoming increasingly important focus of education policy developed to help beginning teachers develop professionally and stay in teaching work force as a way to meet the needs of global economy and social transformation for teaching quality and student learning in many countries. Policy borrowing is a common practice in teacher induction across different countries, Such a policy borrowing allow policymakers in particular countries to access different options and choices in their policy development instead of trial and error. However, it is often done without a careful policy analysis as its base, especially, the analysis that focuses on the problems the borrowed policy intends to solve, social, political, and educational contexts in which it develops, explicit and implicit conceptual assumptions underlying it, its implementation and associated challenges, and its intended and unintended impacts. Without such an analysis as its base, the implementations of policy borrowed from other countries can causes unnecessary financial, human resource, and emotional costs in its context, even if the policy prove to be successful in the other place. This book serves for such needs of policy analysis in the field of teacher induction. It starts with the book editor's overview of the book and its intention. Then, there are 16 chapters each is written by a distinguished scholar or a policy analyst from a particular country that analyzes the focuses, contexts, assumptions, implementation, challenges, and consequences of a specific teacher induction policy developed in their home country and then raise important research questions emerging from their analysis. In the end, an eminent scholar in the field of teacher induction will critically analyze all the chapters for the commonalities and differences from a comparative way and offer important scholarship, policy and practice implications based on of his or her critique. The book is expected to attract readers including scholars, policy makers, practitioners, and graduate students in different countries who have interests in teacher induction research, policy, and practice"-- Provided by publisher.
Keywords: Teacher orientation -- Research.; Mentoring in education.; Education -- Educational Policy & Reform -- General.; Teacher training.; Educational strategies and policy.; elektronické knihy; electronic books